Fatores de risco para recidiva da neoplasia intraepitelial cervical após cirurgia da alta frequência - Helena Rabelo Castro Meira (2014)
Objectives: To evaluate the frequency of recurrence of cervical intraepithelial neoplasia after conization with high frequency surgery and assess the factors are associated with recurrence of cervical intraepithelial neoplasia. Patients and methods: retrospective cohort study (1998-2011), evaluated 287 patients with cervical intraepithelial neoplasia undergoing conization of the cervix. The surgical specimen was sent for histopathological examination, which assessed the degree of lesion margins and glandular involvement. Patients were followed every 6 months with cytology sample collection for HPV DNA, colposcopy and biopsy when indicated. The mean follow-up was 25.1 months. The lesions after surgery, were confirmed by biopsy was considered recurrences. For analysis of the qualitative characteristics was performed univariate analysis using the Kaplan - Meier results associated with the log - rank test. Multivariate analysis was performed by adjusting the Cox model to statistical significance of p - value < 0.05. Results: In the study, 65 (22.6 %) patients had histopathologic diagnosis of recurrence. The recurrence rate in HIV positive patients was higher with a relative risk of 4.45 and CI (2.73 to 7.25). The glandular involvement was associated with recurrence in HF and 2.82 (1.73 to 4.62) and positive margins relative risk of2, 81 and CI (1.69 to 4.65). Conclusions: Recurrence of CIN is associated with positive margins, the HIV seropositivity and glandular involvement. The risk of recurrence in women with HIV virus was significantly higher compared with women not infected with HIV.